Method for the three-dimensional kinematic analysis of the paddling cycle in the flat watter kayaking - M. Espinosa (Asociación Española de Ciencias del Deporte, 2011)
The technique in kayaking is a movement system that is analyzed on the basis of the four corporal positions that the body adopts during a paddling cycle. A case of study is presented in order of establishing the methodology that could be used periodically in the analysis of the paddling cycle to improve the effectiveness in the propulsion of the kayak. The used methods are based on photogrammetric principles of the simultaneous registry of three sequences in video of which are captured the anatomical points that represent the axes of rotation of shoulders, elbows and wrists. The kinematic values in 3D compared left and right: the time, the paddling length, the angles and angular velocities of shoulders and elbows, and the inclination of the arms, in addition the paddling frequency and the boat velocity are calculated. The results are within the reported ranks in Literature, indicating the characteristics of the paddling cycle of the athlete, and if so, indicating the failures in the synchrony and symmetry of the movements. The proposal make possible to evaluate the individual technique within a global process of training. Key Words:three-dimensional analysis, photogrammetry, kayak, paddling cycle